Parasite richness in fish larvae from the nearshore waters of central and northern Chile - Munoz, Gabriela; Landaeta, Mauricio F; Palacios-Fuentes, Pamela; Lopez, Zambra; Gonzalez, Maria Teresa (Folia parasitologica, 2015)
In the present study, we determine the presence of parasites in fish larvae collected from nearshore waters along the northern and central coast of Chile. The parasites were identified to the lowest possible taxonomic level based on morphological and molecular analyses. The fish sample was composed of 5 574 fish larvae. Of these, 3% harboured only larval ectoparasitic copepods whereas no endoparasites were found in the 1 141 fish evaluated for this group of parasites. The parasitic copepods collected were initially classified as 'morphotypes' according to differences in morphological characteristics. They were then analysed using molecular techniques based on the 28S and COI genes. Seven morphotypes of parasitic copepods (mostly at chalimus stages) were recognised: two of the morphotypes belonged to Pennellidae Burmeister, 1835, three to Caligidae Burmeister, 1835 and two were not identified. Only five morphotypes of copepods were analysed using molecular sequences, which confirmed the existence of six species: two pennellids of the genus Trifur Wilson, 1917 and two caligids of the genus Caligus Müller, 1785, plus two additional species that were morphologically different from these taxa. The pennellids were present in several fish species, being generally more prevalent than the caligids, in both the central and northern localities of Chile. Multispecies infections in larval fish were infrequent (< 1%). We conclude that fish larvae were rich in parasites, considering that these hosts exhibited small body sizes and were very young. We suggest that fish larvae could play a role, as intermediate hosts, in the life cycle of the parasitic copepods found.
Keywords: Pennellidae; fish larva assemblage; copepods; intertidal fish; Caligidae